Pembuatan Sistem Penghitung Kecepatan Mobil Listrik Teknik Mesin Unsyiah Berbasis Mikrokontroler Atmega 8535 - Syahriza Syahriza; Masri Ibrahim; Arhami Arhami; Naswadi Naswadi (Jurnal Teknik Mesin Unsyiah, 2015)
Speed measurement equipment is very essential in a vehicle. The speed measurement equipment engineered in this research is specially designed for the electric vehicle of Mechanical Engineering, Syiah Kuala University, which is equipped with microcontroller of atmega 8353. The sensor system utilized is a dc generator which is connected to the front wheel of the electric car. The rotation of the wheel causes the generator to rotate that the generator produces dc electric voltage that the voltage is sent to the microcontroller. In general there are two main base components used for speed measurement equipment which are hardware and software. The software used to support the programming of the equipment is code vision AVR. The reading of input signal, processing and the visual display are designed with code vision AVR programming and c programming language. The test was conducted at the wheel of the vehicle with several steps of rotation speed to know the speed of the vehicle in rpm and convert it into km/hour by calibrating it based on the wheel diameter. The speed data is displayed on an LCD in real time that the driver knows the real speed.